Deceased Members (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1923)
Members whose deaths were reported from April 7, 1924 to April 7 1925 Elected Died 1923 ANDERSON, ANDREW ELMER 1924 1919 ANDERSON, JOHN EDWARD 1924 1923 BENKISER, WILLIAM JACOB 1924 1900 BROOKS, ALFRED H 1924 1900 BROWN, CONY T 1925 1910 BROWN, GILMOUR E 1924 1894 ChAPPELL, HOWARD F 1924 1882 CLARK, W A 1925 1918 CLEAVES, DANIEL LUNT 1924 1883 COLBY, ALBERT LADD 1924 1886 CORNING, C R 1924 1911 CRABTREE, FRED 1925 1875 CREMER, J H 1924 1921 CRONIN, JAMES 1925 1904 DANIEL, WILLIAM B 1924 1891 DOUGHERTY, JOHN W 1924 1920 ESCARDO, HECTOR FLORENCIO 1924 1921 FRANK, PAUL MELVILLE 1924 1920 GILES, ROBERT 1924 1922 GILLETTE, LEWIS SINGER 1924 1918 HARRIS, J W 1924 1902 HARTMAN, T F 1923 1912 HERRMANN, CHARLES E 1924 1892 HILLES, JOSEPH T 1924 1882 HOFMAN, H O 1924 1905 HOVEY, EDMUND O 1924 1923 KIME, EDWIN R. 1924